Local Government and Intergovernmental Relations in Nigeria’s Fourth Republic - Adedire, Solomon Adebayo (Covenant University Journal of Politics and International Affairs, 2016)
The paper examines local government and intergovernmental relations in Nigeria‟s Fourth Republic, with special attention on the period of 1999 to 2014. The paper argues that Local Government is not mutually exclusive of other levels of government and that as such there is bound to be an interaction between the local and other levels of government. The study reveals that intergovernmental relations among the levels of government in the Fourth Republic up to 2014 were in disarray due to the conflicts over issues of tax jurisdiction, revenue allocation, intergovernmental relations, fund transfers, overconcentration of power at the centre, illegal removal of government officials, among other factors. The paper posits that for cordial relationship between the local and other levels of government to take place, the constitutional status of local government must be clearly spelt out, the issue of joint state-local government account should be reversed, election rather than appointment should be the means of choosing leaders at the local level, judiciary should be made to be independent and the undue interference on the local government by the state or federal government has be properly addressed. Also, there should be direct disbursement of federation allocation to all the levels of government.